Examining the effects of abuse on girls in gangs - Ford, Champagne Monique (2008)
The purpose of this study is to encourage further study and attention to girls that are at high risk of becoming members of a gang. The more that can be learned about this group the more can be done to implement appropriate policies and programs to effectively target and assist this population. This study is based on an existing data set that profiled the needs and characteristics of girls that were incarcerated May 1996 at a California Youth Authority facility in Ventura, now called The Division of Juvenile Justice